Rancang Bangun Prototipe Digester Biogas Untuk Menunjang Praktikum Mahasiswa - Subarjo Subarjo (Jurusan Teknologi Pertanian, 2019)
Energy is an essential requirement to support the activities and productive enterprises to produce goods and services. Almost all human activity is highly dependent on energy. Fuel shortages arise because of the level of fuel demand is very high and is increasing every year. While oil revenues are limited and membutukan earth millions of years time for formation. Due to the scarcity of fuel, causing the need of alternative energy that are environmentally become one of the necessities that can not be negotiable. The development of biogas digester technology to utilize and increase the economic value of waste is one with the road use it as raw material for biogas production. It is very suitable if to develop tool called biogas digester biogas or biogas reactor. The observation of the test digester, biogas on days 3 to 7 is not formed, even until day 14. The digester should be maintained in a state abiotis (without direct contact with oxygen; temperatures of 20-30Â°C). Gas began formation at day 14, and the highest gas increase at day 18 to 21, while the rate of formation of methane gas (biogas) at 13. the image that is on day 18 of 8.8 scale/cm and then on day 21 and 30 begin to decrease formation gas. the presence of the added value derived from manure waste created biogas can be used for cooking or lighting instead of electric energy.Â Keywords: digester, biogas, fermetation, anaerobic